2023
DOI: 10.1051/0004-6361/202244243
|View full text |Cite
|
Sign up to set email alerts
|

Degree of stochastic asymmetry in the tidal tails of star clusters

Abstract: Context. Tidal tails of star clusters are commonly understood to be populated symmetrically. Recently, the analysis of Gaia data revealed large asymmetries between the leading and trailing tidal tail arms of the four open star clusters Hyades, Praesepe, Coma Berenices, and NGC 752. Aims. As the evaporation of stars from star clusters into the tidal tails is a stochastic process, the degree of stochastic asymmetry is quantified in this work. Methods. For each star cluster, 1000 configurations of test particles … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The analysis here based on the inner tidal tail data as obtained by the CP method shows the Hyades to be consistent with the null hypothesis while the Praesepe (a 4.9 sigma deviation) and COIN-Gaia 13 (an 8.39 sigma deviation) are not. Combining the available information: The extended tidal tails of the Hyades are in > 5 sigma tension with the null hypothesis (Kroupa et al 2022;Pflamm-Altenburg et al 2023), and the inner tidal tails of the Praesepe are in 4.9 sigma and of COIN-Gaia 13 in > 5 sigma tension with the null hypothesis. The asymmetry is the same in all three cases, namely, the leading tail contains significantly more stars than the trailing tail.…”
Section: The Cluster Coin-gaia13 Needs Special Attentionmentioning
confidence: 88%
See 3 more Smart Citations
“…The analysis here based on the inner tidal tail data as obtained by the CP method shows the Hyades to be consistent with the null hypothesis while the Praesepe (a 4.9 sigma deviation) and COIN-Gaia 13 (an 8.39 sigma deviation) are not. Combining the available information: The extended tidal tails of the Hyades are in > 5 sigma tension with the null hypothesis (Kroupa et al 2022;Pflamm-Altenburg et al 2023), and the inner tidal tails of the Praesepe are in 4.9 sigma and of COIN-Gaia 13 in > 5 sigma tension with the null hypothesis. The asymmetry is the same in all three cases, namely, the leading tail contains significantly more stars than the trailing tail.…”
Section: The Cluster Coin-gaia13 Needs Special Attentionmentioning
confidence: 88%
“…By applying Milgromian and Newtonian gravitational models to these data, Kroupa et al (2022) showed that while the full tails of the Praesepe, Coma Berenices and NGC 752 are consistent with Newtonian symmetry, the data are also consistent with Milgromian gravitation. The full-length tails of the Hyades cluster, however, are inconsistent with the Newtonian symmetry at more than 5 σ confidence (see also Pflamm-Altenburg et al 2023), while being consistent with Milgromian gravitation. The Galactic bar does not influence the evolution of star clusters orbiting at Galactocentric distances larger than ≈ 4 kpc (Rossi & Hurley 2015).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Dynamical friction offers an alternative way to study the small-scale effects induced by hypothetical microphysical properties of DM (Hui et al 2017;Hartman et al 2021). Moreover, its applications are much broader than DM inference, as dynamical friction is the underlying phenomenon that influences a wide variety of astrophysical systems, from stellar streams and globular clusters to the orbits of satellite galaxies and galaxy merging times (Kipper et al 2019(Kipper et al , 2020Pflamm-Altenburg et al 2023;Correa Magnus & Vasiliev 2022).…”
Section: Introductionmentioning
confidence: 99%